THE STATEMENT OF REALIZATION AND LIQUIDATION. - Edmondson, V. G. (The Accounting Review, 1955)
The purpose of the article is to present a form for the Statement of Realization and Liquidation, and to present a study and comparison of the form suggested with the other forms which have been used in the past. When a Receiver in Equity is appointed by the court to take charge of the affairs of an insolvent firm, an interesting accounting problem presents itself. This problem is the proper classification of the many kinds of transactions performed by the receiver. During the period of a "friendly receivership" it is desirable to classify the transactions pertaining to operations, and the transactions dealing with partial liquidation. Unless a clear-cut distinction is made between the results of operations and of partial liquidation, it may prove difficult for the court to determine wisely the future of the organization. To report upon these two kinds of transactions, as well as to show the change in the Assets and Liabilities of the business during receivership, a Statement of Realization and Liquidation may be prepared.